Identification of the pop-up acceleration waveform signal: a case study - Lowrie, J. R. H.; Sayers, M. G. L. (ISBS Proceedings Archive (Michigan), 2022)
The purpose of this case study was to assess the feasibility of using accelerometers to identify and analyse the acceleration waveform signals of the pop-up movement. An experienced male recreational surfer performed 10 dry-land pop-ups with accelerometers (1000 Hz) attached to the sacrum and lateral aspect of each shank. The waveform signals of the pop-up were successfully identified at each instrumentation site using a combination of acceleration and video data. Several movement events that occurred during the pop-up were also able to be detected within each of the mean resultant acceleration signals. These findings suggest that accelerometers can viably be used to detect and analyse the waveform signals of the pop-up. This provides initial evidence that accelerometers are a suitable tool for collecting kinematic data of surfing performances.